Tinjauan Kode Etik Aparatur Sipil Negara Dalam Kaitannya dengan Korupsi di Instansi Pemerintahan - Mohamad Yuflih (CV Rewang Rencang, 2022)
Research by Indonesian Corruption Watch shows that corruption is one of the bad images of the State Civil Apparatus. On the other hand, Permendagri No. 15 of 2020 concerning the Code of Ethics for State Civil Apparatuses regulates the code of ethics that forms the basis for ASN performance. This study examines the relationship between corruption and the ASN Code of Ethics with the results of the study concluding that the ASN code of ethics prohibits the practice of benefiting oneself and one's class for ASN with the threat of dishonorable dismissal to the imposition of sanctions regulated through various regulations. Keywords: State Civil Apparatus, Corruption, Code of Ethics